Analysis of Spanish realia in the novel of E. Mendoza “No word from gurb” - O S Lilikovich (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2013)
The article deals with analysis of realia in Spanish culture. The analysis is based on the context of contemporary Spanish novel “No Word from Gurb” by E. Mendoza.